Rechtsvacuum In The Conviction Of The Criminal Act Of Bribery Assistance - Ahmad Hadi Prayitno (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
Bribery assistance perpetrators have an essential function in a series of incidents of bribery. It has juridical consequences regarding the need for a clear and definite conviction for them. The ambiguity of Article 15 of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes, given the position of perpetrators of bribery assistance, has had a major impact on the rechtsvacuum in the criminal justice system on bribery crimes. Based on the study of this normative method article, it was found that criminalization in bribery cases, in fact, does not only include active and passive perpetrators of bribery, but the existence of perpetrators of bribery assistance cannot be ruled out either. There is the fact that the provision for bribery assistance in Article 15 of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes has resulted in a rechtsvacuum in terms of conviction in bribery cases. This situation has clearly resulted in uncertainty regarding the criminal sanction imposition for bribery assistance perpetrators.